Association between vegetable intake and major depressive disorder: results from National Health and Nutrition Examination Survey 2005–2018 and bidirectional two-sample Mendelian randomisation - Qi Wang; Zhaoxing Ou; Jiamin Chen; Liujun Li; Yuzhuo Chen; Dalin Ye (Public Health Nutrition)
Abstract